2018
DOI: 10.1002/elps.201800087
|View full text |Cite
|
Sign up to set email alerts
|

A closer look at Verogen's Forenseq™ DNA Signature Prep kit autosomal and Y‐STR data for streamlined analysis of routine reference samples

Abstract: Massively parallel sequencing (MPS) provides forensic DNA laboratories an option to overcome the limitations associated with CE and current STR assays. Verogen's MPS Forenseq DNA Signature kit concomitantly amplifies 27 autosomal, 7 X-, and 24 Y-STRs. In addition, 94 identity, 56 ancestry, and 22 phenotypic-informative SNPs are included for a total of over 200 markers in one multiplex. An internal validation of this platform was conducted using reference samples to investigate whether the Forenseq™ DNA Signatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 22 publications
3
29
0
Order By: Relevance
“…2 and S1). In general, results for the ForenSeq DNA Signature Prep Kit aSTR sensitivity were comparable to CE-based STR kits [58][59][60][61] and in line with earlier published MPS studies [1,3,4,14,54].…”
Section: Sensitivitysupporting
confidence: 88%
See 1 more Smart Citation
“…2 and S1). In general, results for the ForenSeq DNA Signature Prep Kit aSTR sensitivity were comparable to CE-based STR kits [58][59][60][61] and in line with earlier published MPS studies [1,3,4,14,54].…”
Section: Sensitivitysupporting
confidence: 88%
“…With the emergence of massively parallel sequencing (MPS) technologies, molecular genetic tools have been developed to characterise the nucleotide sequence of short tandem repeat (STR) markers that have so far been analysed using fragment sizing by capillary electrophoresis (CE) [1][2][3][4][5][6][7]. As is common practise in forensic genetics, such novel tools undergo detailed evaluation [3,[8][9][10][11][12] and validation [1,13,14] prior to their application in casework. Recent population studies have shown that sequencing of STRs lead to an increased power of discrimination compared to commonly used CE sizing by a) illustrating micro-variant structures and b) identifying sequence variations located in the repeat-(isometric variants; alleles of identical size but different in internal sequence) or flanking region [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…sequencing error, PCR error, DNA damage, pseudogenes) could be consistently distinguished from authentic signal. We have employed methods for doing exactly that in other NGS studies [23,56,57]. However, these analyses have been largely manual, which is not suitable to a production environment.…”
Section: Discussionmentioning
confidence: 99%
“…The large-scale performances and functional tests had been widely validated for the ForenSeq™ DNA Signature Prep Kit, the DNA Primer Set A (DPMA, 152 loci totally: 27 common, forensic autosomal STRs, 24 Y-STRs, 7 X-STRs, and 94 identity informative SNPs) and the DNA Primer Set B (in total 230 loci: DMPA plus 22 phenotypic informative SNPs and 56 biogeographical ancestry SNPs), which also include robustness, reproducibility, species specificity, consistency and sensitivity of detection [40][41][42][43][44][45][46][47]. In addition, the applicability of the DNA Signature Prep Kit had been evaluated and verified on challenging samples, DNA mixture, degradative DNA [48][49][50], formalin-fixed paraffin-embedded tissues [49,51], and remains of skeletons and bones [48,[52][53][54], to extend the applications for forensic sciences [55][56][57][58][59][60][61][62][63][64][65][66][67][68]. Hence, on the basis of the sufficient validations of the stability and homogeneity, more essential data of worldwide populations are needed urgently at present to improve the standard experimental procedures, promote the efficiencies of MPS-based system, and strengthen and unify the contacts between capillary electrophoresis-based (CE-based) and MPS-based data for the basic and extended applications of forensic sciences and others.As the aborigines in Hainan island where was the entrances to East Asia (either the southern entrance from Indo-China peninsula or the northern entrance from Central Asia) [12,[69][70][71], Hainan...…”
mentioning
confidence: 99%